تجاوز دﹶين التاريخ الاستعماري في "موسم للمغامرة" للكاتب جورج لامينغ - عطيّة مجدة (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يقدم هذا البحث تفسيراً جديداً لنظرية الكاتب الكاريبي جورج لامينغ حول اللغة, بوصفها إستراتيجية للمقاومة, وذلك في ضوء مناقشة مفهوم الذات السلعية. بشكل خاص, يمكن قراءة رواية لامينغ "موسم للمغامرة" كعمل نموذجي عن المفهوم الثوري لشراء الذات و الذي يتبنى اللغة بوصفها وسيلة لمعارضة الدﹶين المفروض والموسوم بالتاريخ الاستعماري. إذ تتسم اللغة في هذه الرواية بصفة التنقيح و ذلك لإتباعها نهج المراجعة لأصل الفرد وماضي الأمة. يمكن القول أن مثل هذا المفهوم التنقيحي للغة يقدّم ما يمكن تسميته بسلالة التعارض في نهاية المطاف. في هذا السياق, تتجاوز كلّ من البنية الموضوعية و السردية لرواية "موسم للمغامرة" على حد سواء ما يمكن تسميته بالدﹶين الإستعماري الأوروبي الذي يتعلق بتوصيف التاريخ, كما وتقدّمان خطاباً نصياً لتأريخ المقاومة. تعتمد هذه القراءة لرواية "موسم للمغامرة" على النظريات الحديثة عن مفهوم الدﹶين بالإضافة إلى إستراتيجيات لامينغ للمقاومة اللغوية الواردة في كتاباته غير النثرية. This article re-interprets George Lamming’s theorization and presentation of language as a strategy of resistance in light of investigating the notion of the commodified self. In particular, Lamming’s Season of Adventure can be addressed as a narrative of rebellious self-purchase that construes language as a medium of historical dissent to the imposed debt of colonial history. Language in Season of Adventure is shaped by revision as it retraces both the genealogy of the individual and the past of a nation. Arguably, such a revisionary conception of language ultimately projects an alternative genealogy of opposition. In this respect, both the thematic and narrative structure of Season of Adventure transcends the European debt of history and presents a textual counter-discourse that articulates a historiography of resistance. Recent theories on the logic of debt and Lamming’s strategies of linguistic resistance featured in his non-fiction writings are central to the premise of this reading of Season of Adventure